SUSTAINABLE DEVELOPMENT GOALS: ANALYSIS FACTORS NO POVERTY IN JAVA - Jetlikhsan, Daud; Boedirochminarni, Arfida (Institut Teknologi dan Bisnis Asia Malang, 2024)
The Sustainable Development Goals are in line with Indonesia's vision and mission. One of the 17 SDGs, is zero poverty. Poverty gets the most attention because all the SDGs are some kind of effort to achieve the goal of